Survey of ICT and Education in Africa : Djibouti Country Report - Hare, Harry (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev) - supported survey of the Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. Djibouti boasting a digital telecommunications network and connections to the rest of the world through undersea optical fibre that are much admired in the region. Two-thirds of the population is urban, and ICT services are readily available in urban areas. The country has a good relationship with most western donors. All these factors support Djibouti's efforts to modernize their education sector. With an ongoing reform program, Djibouti has mostly focused on developing and improving the physical infrastructure and other non-ICT resources, including building new classrooms and providing textbooks. In higher education, a key focus has been on producing skilled teachers and encouraging out-of-school youths to get vocational training. At a policy level, ICT is a component of the national ICT policy, which was developed by the Ministry of Communication. Djibouti needs a sector-specific policy for the adoption of ICT in education, together with an implementation plan that will take advantage of the available enablers including the telecommunication network.